Predicted acoustical performance of multi-unit splitter silencers - Ramakrishnan, R.; Watson, W.R. (Canadian Acoustics, 1990)
Passive silencers with acoustic fill are commonly used to reduce the fan noise in rectangular ducts of conventional air-handling systems. Design procedures for silencer performance evaluation of simple configurations have been available for some time. Design curves for a wide variety of rectangular silencers were made available recently. Many methods for predicting silencer insertion loss assume the silencers to be a single unit. In many air-handling systems however, the duct is divided into many small units by installing splitters in the duct. Predicted insertion loss results for multi-unit splitter silencers are presented in this paper. Multi-unit silencer performance is compared to that of a single unit within the full duct. The accuracy of using a single-unit model to represent the different types of conventional rectangular silencers is also presented